Hospital outcome of percutaneous coronary stenting in long segment lesions - Uddin, M. Bashir; Siddique, A. B.; Munir, M. Shirajum; Uddin, Refaz; Masud, Abdullah Al; Ahmed, Firoz; Zahid, M. Abu; Islam, Mazharul (International Journal of Advances in Medicine, 2021)
Background: Coronary heart disease is increasing at an alarming rate among elder people in Bangladesh. For long segment lesion in heart, percutaneous coronary intervention is now a common procedure with great success rate. The aim of this study was to assess immediate outcome of percutaneous coronary stenting of long segment lesions. Methods: This prospective observational study was conducted at the Department of cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh during the period from January 2005 to December 2006. The sample size was 100 patients undergoing PCI of long and short coronary lesions. Results: No complications found in 82.0% and 88.0% of cases in group I and II respectively. Coronary dissection occurred in 6% and 4% cases in group I and II respectively. ST elevation and pathological Q were 46.0% in pre and 50.0% in post PCI period in group I. In group II patients 48.0% in pre and 52.0% in post PCI period showed ST elevation and pathological Q wave. ST depression and/or T inversion was 18.0% in pre and 16.0% in post PCI period in group I, in group II this value was 22.0% and 14.0% respectively. In group I patients, CK-MB increased from 24.33±7.72 U/l in baseline to 43.30±10.99 U/l 6-8 hrs after procedure and before discharge CK-MB decreased to 31.91±11.17 U/l. In the group II patients, it increased from 25.42±5.84 U/l in baseline to 39.38±6.98 U/l 6-8 hrs after procedure and before discharge CK-MB decreased to 29.64±8.21 U/l. Conclusions: This study concludes that the immediate outcome of long segment coronary stenting is safe and highly effective.